The welfare effect of flat income tax reform: the case of Bulgaria - Aleksandar Vasilev (Eastern European Economics, 2015)
This paper is a first attempt to provide a quantitative evaluation of the welfare gains resulting from the introduction of flat income taxation in Bulgaria in 2008. Using a calibrated micro-founded endogenous growth model with physical and human capital accumulation to Bulgarian data, a computational experiment is performed to quantify the dynamic welfare effect of progressive income taxation vis-a-vis flat income taxation. The model demonstrates that significant welfare gains, measured in terms of per-period consumption, can be realized with the introduction of flat income taxation. In addition, these welfare gains increase proportionally with the length of the time horizon considered. Finally, sensitivity analysis was performed to demonstrate that the results obtained are robust.
Additional information: this is the accepted version of the article that appeared in Eastern European Economics
Keywords: H22; D91; O41; 330; Taxation; Endogenous growth; Human capital; Welfare gains